A Newer Approach in the Management of Cough: A Review on Levodropropizine - Prasanna K Thomas; Pramod Jog; Nitin R Vohra; Krishna C Veligandla; Uttam Anup Petare (Journal of Respiratory Diseases, 2023)
Safe and effective antitussive therapy remains a significant area of unmet need for cough management. Antitussive drugs are commonly used cough suppressants and include centrally acting (opioids and non-opioids) cough suppressants and peripherally acting antitussives. Authors searched PubMed, Google Scholar and additional studies from reference lists via cross-referencing to identify studies assessing levodropropizine for the treatment of cough. Of the 748 studies identified, 13 were included. Recent clinical evidence, guideline recommendations and findings from this review suggest that levodropropizine is a peripheral antitussive which reduces cough intensity, frequency, and nocturnal awakenings in children and adults and provides better efficacy outcomes with a more favourable risk/benefit ratio compared to centrally acting antitussive agents which pose greater safety concerns and present an unacceptable risk–benefit profile. This review is aimed at Indian primary care physicians for making effective cough management decisions where the clinical evidence needs to be translated to clinical practice. Key Messages The usage of currently available centrally acting antitussive agent is greatly limited by their central depressing action and frequent side effect. The findings of this review indicate that levodropropizine is an effective antitussive agent and well tolerated in the management of cough in patients of all ages.
Keywords: Antitussive drugs